(untitled) (Journal of the College of Basic Education, 2022)
There is no doubt that the crime of theft is a social phenomenon known to ancient and modern human societies, and statistics indicate that the wave of this phenomenon is spreading, and it is raising interest and in a way that has occupied the minds of thinkers and the efforts of researchers. Scientists in their various specializations did not find a single society in any era other than this type of criminal behavior besides normal or sound behavior, because virtue and vice are a common title in every human society. The crime of theft is a social problem that obligated human societies in their struggle and competition to satisfy their needs. Therefore, social norms, divine laws and positive laws were monitored with great interest, and the perception of the thief and the theft varied in different societies and eras. There are many opinions regarding determining the factors that cause this criminal behavior (theft). Some of them attributed it to the absence of social justice and class disparity between members of society, and some of them attributed it to the hatred of members of society to the wrong policies of the ruling authority, and some of them attributed it to the weak economic level of the individual that leads to the difficulty of its occurrence On the necessities of life and leaves room for searching in crooked ways. From the side of protecting public funds criminally, there were various legislations to put criminal penalties on individuals who steal or infringe public funds. The French legislator considered it a crime against honor and the Egyptian legislator considered it a crime of aggression on public money, and the Iraqi legislator gave it special attention in a group Legislations whose purpose is to protect public money from theft, damage, or sabotage of it, distributed between Law 111 of 1969 and other legislation. The researcher reached a set of conclusions, including: 1-The crime of stealing from public money is the most important crime among the crimes against money. The researcher presented a set of recommendations in the light of the results of the research, including: 1-The criminal legislator must make amendments, and introduce some legal texts on crimes and penalties, to give more criminal protection to public funds from theft.